The Strategy of Islamic Religious Education Teachers in Overcoming Students' Difficulties in Reading the Qur'an at SMP IT Masjid Syuhada Yogyakarta - Hafidz; Isnaya Arina Hidayati‎; Nurul Latifatul Inayati‎ (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to identify and analyze the strategies used by Islamic Religious Education teachers in overcoming students' difficulties in reading the Qur'an at SMP IT Masjid Syuhada Yogyakarta. The method used is descriptive qualitative with a phenomenological approach. The research results show that at SMP IT Masjid Syuhada, the tilawati method is used by teachers as a strategy to help students who have difficulty reading the Qur'an. The teachers strive to make the learning process more effective and enjoyable so that the students can read the Quran correctly and fluently using the rost technique. With this method, it is hoped that students will not only learn to read the Qur'an but also understand the contents of the holy book. The tilawati method has several advantages and disadvantages. This method balances classical and individual learning, and uses a variety of songs to maintain student interest. However, some weaknesses that need to be considered are the longer time requirement, limited facilities, the need for trained teachers, and the challenge of adapting this method for students with varying abilities.